2012
DOI: 10.1590/s0104-07072012000200014
|View full text |Cite
|
Sign up to set email alerts
|

Saberes e práticas populares de cuidado em saúde com o uso de plantas medicinais

Abstract: Objetivou-se conhecer a origem dos saberes e das práticas sobre o uso terapêutico de plantas medicinais, por moradores de comunidade da região central do Estado do Rio Grande do Sul, Brasil. Trata-se de uma pesquisa qualitativa, com coleta de dados por meio de entrevista semiestruturada e observação participante. Os entrevistados foram selecionados por meio da rede de relações dos mesmos. Para análise dos dados foi utilizada a análise temática. Constatou-se que o aprendizado do uso e manipulação de plantas med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
51

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(83 citation statements)
references
References 6 publications
(11 reference statements)
0
17
0
51
Order By: Relevance
“…It is believed that the care provided by means of medicinal plants is beneficial to human health, as long as the user has prior knowledge of their effects, risks and benefits. 21 A study on the contributions of phytotherapy to the quality of life has shown that the advantages of phytotherapy have been highlighted at the expense of the disadvantages, being used by the users due to its effectiveness, low cost, reduction of side effects and the stimulus to the acquisition of health habits. 22 A study on the contributions of herbal medicine to the quality of life has shown that the herbal medicine advantages stood out over the disadvantages, being used due to its effectiveness, low cost, reduced side effects and because it stimulates the acquisition healthy life habits.…”
Section: Resultsmentioning
confidence: 99%
“…It is believed that the care provided by means of medicinal plants is beneficial to human health, as long as the user has prior knowledge of their effects, risks and benefits. 21 A study on the contributions of phytotherapy to the quality of life has shown that the advantages of phytotherapy have been highlighted at the expense of the disadvantages, being used by the users due to its effectiveness, low cost, reduction of side effects and the stimulus to the acquisition of health habits. 22 A study on the contributions of herbal medicine to the quality of life has shown that the herbal medicine advantages stood out over the disadvantages, being used due to its effectiveness, low cost, reduced side effects and because it stimulates the acquisition healthy life habits.…”
Section: Resultsmentioning
confidence: 99%
“…The transmission of knowledge on medicinal plants is sustained by the relation of affection between the women-mother figure and the child, in an attempt to pass the knowledge on to the next generation. 14 The first contact with the use of medicinal plants was, according to respondents, aimed at the cure of diseases. These experiences were mentioned as of great significance, because satisfactory results were reported, which encouraged the subjects to use plants routinely.…”
Section: "I Learned From My Family"mentioning
confidence: 99%
“…This finding corroborates the study conducted with residents of the coverage area of a Family Health Unit, in which a close relationship becomes evident between women and the plants, for their use was the main therapeutic resource used to treat people's health and of their families. 14 The care of the family members is usually assigned to women, and this female predominance highlights the importance of women in the transmission of knowledge between generations and the responsibility for the implementation of health care in the family, making use of medicinal plants for its realization.…”
Section: "I Learned From My Family"mentioning
confidence: 99%
“…Entretanto, deve-se primar pela qualidade do material vegetal utilizado, evitando exposição a riscos por aquisição de produto impróprio para o consumo. 27,28 Quando questionados sobre os principais desafios para implantação do programa de fitoterapia, os entrevistados destacaram: o compromisso do gestor principal; a necessidade de parcerias com centros de ensino e pesquisa; a aceitação dos prescritores; a disponibilidade de recursos humanos; a regulamentação para o serviço; o incentivo à comunidade; o apoio da Secretaria Municipal de Saúde; a capacitação dos profissionais; e a estrutura adequada na unidade (Figura 1). Observa-se que a estrutura física da unidade de saúde e a capacitação profissional foram os desafios mais referidos pelos diretores (21% e 18%, respectivamente).…”
Section: "Há Alguns Anos Atrás Em Outra Gestão Houve Um Início De Punclassified